The Relationship between Breakfast Habits and Mathematics Learning Concentration among Seventh-Grade Students at MTs Al-Amin Kampung Pajak - Arni Apriani; Irvan Irvan (JMEA : Journal of Mathematics Education and Application, 2025)
This study aims to examine the relationship between breakfast habits and concentration in mathematics learning among seventh-grade students at MTs Al-Amin Kampung Pajak. The research employed a quantitative approach with a correlational design. Data were collected from 59 students using structured interviews, supported by teacher observations. The instrument underwent content validation by experts and was refined through a pilot test prior to implementation. The collected data were categorized into two nominal variables: breakfast habits (had breakfast vs. skipped breakfast) and concentration levels (high vs. low). The Phi coefficient (φ) was used for statistical analysis, supported by the chi-square test. The findings show a perfect correlation (φ = 1.0) between breakfast habits and learning concentration. All students who had breakfast exhibited high concentration, while all students who skipped breakfast demonstrated low concentration. The chi-square test yielded a value of 59, which exceeds the critical values at both 5% and 1% significance levels. These results indicate a statistically significant and strong positive relationship between breakfast consumption and mathematics learning concentration. The study concludes that breakfast is a critical external factor that enhances students’ cognitive readiness and supports academic success, particularly in mathematics.